Determinants of malaria infections among children in refugee settlements in Uganda during 2018-2019 - Henry Musoke Semakula; Song Liang; Paul Isolo Mukwaya; Frank Mugagga; Monica Swahn; Denis Nseka; Hannington Wasswa; Patrick Kayima (BMC, 2023)
Abstract Background While 5% of 247 million global malaria cases are reported in Uganda, it is also a top refugee hosting country in Africa, with over 1.36 million refugees. Despite malaria being an emerging challenge for humanitarian response in refugee settlements, little is known about its risk factors. This study aimed to investigate the risk factors for malaria infections among children under 5 years of age in refugee settlements in Uganda. Methods We utilized data from Uganda's Malaria Indicator Survey which was conducted between December 2018 and February 2019 at the peak of malaria season. In this national survey, household level information was obtained using standardized questionnaires and a total of 7787 children under 5 years of age were tested for malaria using mainly the rapid diagnostic test. We focused on 675 malaria tested children under five in refugee settlements located in Yumbe, Arua, Adjumani, Moyo, Lamwo, Kiryadongo, Kyegegwa, Kamwenge and Isingiro districts. The extracted variables included prevalence of malaria, demographic, social-economic and environmental information. Multivariable logistic regression was used to identify and define the malaria associated risk factors. Results Overall, malaria prevalence in all refugee settlements across the nine hosting districts was 36.6%. Malaria infections were higher in refugee settlements located in Isingiro (98.7%), Kyegegwa (58.6%) and Arua (57.4%) districts. Several risk factors were significantly associated with acquisition of malaria including fetching water from open water sources [adjusted odds ratio (aOR) = 1.22, 95% CI: 0.08-0.59, P = 0.002], boreholes (aOR = 2.11, 95% CI: 0.91-4.89, P = 0.018) and water tanks (aOR = 4.47, 95% CI: 1.67-11.9, P = 0.002). Other factors included pit-latrines (aOR = 1.48, 95% CI: 1.03-2.13, P = 0.033), open defecation (aOR = 3.29, 95% CI: 1.54-7.05, P = 0.002), lack of insecticide treated bed nets (aOR = 1.15, 95% CI: 0.43-3.13, P = 0.003) and knowledge on the causes of malaria (aOR = 1.09, 95% CI: 0.79-1.51, P = 0.005). Conclusions The persistence of the malaria infections were mainly due to open water sources, poor hygiene, and lack of preventive measures that enhanced mosquito survival and infection. Malaria elimination in refugee settlements requires an integrated control approach that combines environmental management with other complementary measures like insecticide treated bed nets, indoor residual spraying and awareness. Graphical Abstract